Novel Gene Therapy Approaches - Wei, Ming; Good, David (IntechOpen, 2013)
Gene therapy has the potential to be a tailor-made therapeutic with increased specificity and decreased side effects that can offer a "cure" for many disorders. The aim of this book is to provide up-to-date reviews of the rapidly growing field of gene therapy. Chapters cover a large range of topics including methods of gene delivery, and identification of targets with several papers on cancer gene therapy. If more people become aware of the true nature and potential of gene therapy, perhaps we can achieve the full benefit of such an innovative approach for the treatment of a range of diseases, including cancer.